2021
DOI: 10.3280/ecag2-2021oa12184
|View full text |Cite
|
Sign up to set email alerts
|

Comparison study of agricultural insurance government subsidy and farmers' self-subsistent premium in Indonesia

Abstract: Agricultural Insurance as an embodiment of farmer protection and empowerment is carried out with The Rice Farming Business Insurance (AUTP) facility with an insurance premium scheme by the Government of 80% and 20% by farmers. This study aims to simulate the AUTP premium based on government's subsidy and farmers' self-subsistent premium. The simulation test used panel data estimates in Indonesia Province during 2016-2019. The AUTP premium simulation was identified through the Moderating Regression Analysis (MR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
4
0
1
Order By: Relevance
“…In addition to that, there is also an aspect of farmers' independence to not depend on government subsidy for premiums by 80 %. Moreover, Yusuf et al (2021) stressed that the implication of government policy to encourage farmers' independence to participate in paying premiums must be in accordance with the information system of ownership of insured land. Therefore, the governance of farmers' self-subsistent premium payment must be supported with a good land database.…”
Section: Central/regional Governmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to that, there is also an aspect of farmers' independence to not depend on government subsidy for premiums by 80 %. Moreover, Yusuf et al (2021) stressed that the implication of government policy to encourage farmers' independence to participate in paying premiums must be in accordance with the information system of ownership of insured land. Therefore, the governance of farmers' self-subsistent premium payment must be supported with a good land database.…”
Section: Central/regional Governmentmentioning
confidence: 99%
“…This is because the implementation of indemnity-based agricultural insurance contracts can provide opportunities for moral hazard and adverse selection in andemic areas. A study conducted by Yusuf et al (2021) revealed that the target of subsidized AUTP land must consider the risk profile to maintain the sustainability of the insurance company. Its implementation is not only carried out in endemic areas -anti-selection.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there are some weaknesses in the implementation of agricultural insurance in Indonesia. First, field socialization is felt to be still not very massive, especially to understand farmers about the benefits, procedures, and benefits of this agricultural insurance program [9][10][11][12][13]. Even though the government, in coordination with related institutions at the district/city level, has programmed several agendas for the socialization of agricultural insurance throughout the year, including providing a special budget allocation for a separate agricultural insurance socialization program.…”
Section: Introductionmentioning
confidence: 99%
“…In calculating the premium, the organizers only base it on one cause, such as rainfall, so it is called agricultural insurance based on the rainfall index. In addition, the amount (price) of the premium also depends on the amount (large) of the insured value and other factors such as interest rates and the time period for data formation (Yusuf et al, 2021;Sujarwo, 2017;Dartanto et al, 2020).…”
Section: Introductionmentioning
confidence: 99%